Influence of Brevibacillus borestelensis strains on phytoremediation potential and biomolecules contents of Jatropha curcas on diluted chromium sludge soil. (October 2022) - Narayanan, Mathiyazhagan; Muthusamy, Muthusamy; Alshiekheid, Maha; Sabour, Amal; Lan Chi, Nguyen Thuy; Pugazhendhi, Arivalagan
Abstract: This study was carried out in order to find an environmentally friendly solution to recover the abandoned Cr-enriched sludge soil, which causes a variety of environmental issues. Hence, in this research the influence of pre-identified Brevibacillus borstelensis UTM105 and Brevibacillus borstelensis AK2 coated Jatropha curcas seed in phytoremediation process with various treatment groups (group A to F) under greenhouse condition. Furthermore, their influence on growth, biomolecules (total proteins and total chlorophyll) content, and antioxidant activity of J. curcas during the phytoremediation process were analyzed. Surprisingly, the outstanding phytoremediation was recorded in group F treatment. In these groups, Group E. accompanied it, and the Cr was reduced by up to 31.17% and 25.65%, respectively, in treated soil after 90 days of treatment. Among these two bacterial strains, the B. borstelensis AK2 had greatest effect on J. curcas growth, the yield of biomass, total protein, total chlorophyll, and antioxidant activity and it followed by B. borstelensis UTM105. These phytoremediation potential of J. curcas was effective at soil diluted with fertile and xenobiotics free soil with dilution ratio of 50:50 and followed by 75:25 ratio. Because under undiluted Cr sludge soil condition seed germination has not occurred even though the seed has been coated with potential bacterial strains and soil blend with sterilized goat manure. Hence, under diluted conditions J. curcas seed coated with B. borstelensis AK2 showed an outstanding phytoremediation process. Hence, this approach can be applied to a field study to assess the metal removal potential of this sustainable approach. Highlights: First report of J. curcas phytoremediation on abandoned Cr sludge soil of TCCL. First report of J. curcas seed coated by B. borstelensis strains for phytoremediation. B. borstelensis AK2 showed significant influence of J. curcas for phytoremediation. J. curcas showed excellent Cr removal in 50:50 dilution ratio of Cr sludge soil. Reduced 31.17% of Cr metal from diluted Cr sludge soil in 90 days of phytoremediation.